Protective Effects of Punicalagin on Osteoporosis by Inhibiting Osteoclastogenesis and Inflammation via the NF-κB and MAPK Pathways - Wang, Wei; Bai, Jiaxiang; Zhang, Wenhao; Ge, Gaoran; Wang, Qing; Liang, Xiaolong; Li, Ning; Gu, Ye; Li, Meng; Xu, Wei; Yang, Huilin; Xu, Yaozeng; et al. (Frontiers in Pharmacology, 2020)
Postmenopausal osteoporosis is a worldwide disease characterized by reduced bone mineral density and increased fracture risk. Inflammatory bone loss due to excessive osteoclast bone resorption is significant in the pathogenesis and development of osteoporosis. Punicalagin (PUN) is a pomegranate fruit derivative and has potential anti-inflammatory effects. However, the effect of PUN on osteoporotic bone loss has yet to be clarified. In this study, we investigated the effect of PUN on RANKL-induced osteoclast formation and bone resorption in vitro, as well as its potential therapeutic effect on ovariectomized-induced bone loss in vivo. PUN was demonstrated to suppress osteoclast formation and bone resorptive function dose-dependently, while osteoclast-specific genes were also downregulated by PUN. In vivo micro-CT and histopathological staining showed that the OVX procedure led to significant bone loss characterized by decreased bone parameters and increased osteoclast numbers, while PUN treatment dramatically prevented these changes. Furthermore, PUN treatment effectively inhibited proinflammatory cytokine expression in vitro. Mechanistically, PUN maintained bone mass via suppressing NF-κB and MAPK signaling pathway activation. Collectively, our observations provide evidence that PUN is a potential candidate for the treatment of osteoporosis.